The Implementation of Team Games Tournament-Based Peer Tutoring for Problem-Solving Ability in Fifth-Grade English Learning - Diah Sinta Sri Berlianti; Patria Handung Jaya (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2026)
Abstract: Elementary students still face challenges in developing problem-solving ability in English learning due to conventional teaching methods such as teacher-centered instruction and lecturing which make students passive learners. This issue requires innovative and engaging learning models that can increase student participation, motivation, and learning outcomes. This quantitative experimental study investigates the effectiveness of TGT-based peer tutoring in enhancing V grade students’ problem-solving ability in English. The study involved 50 students of Muhammadiyah Elementary School Karangploso, divided equally into an experimental class (25 students) and a control class (25 students). Data were collected using a descriptive test designed according to Polya’s problem-solving indicators and analysed through normality, homogeneity, and independent sample t-tests using SPSS 30. The results demonstrated a significant difference between the two groups, with the experimental class achieving an average post-test score of 83.40, compared to 61.00 in the control class. These findings indicate that peer tutoring based on TGT is more effective than conventional teaching methods in improving students’ problem-solving abilities. In conclusion, the TGT based Peer Tutoring model offers a strategic method for improving the quality of English instruction and strengthening problem-solving competence in an elementary school context. Abstrak: Siswa sekolah dasar masih menghadapi tantangan dalam mengembangkan kemampuan memecahkan masalah dalam pembelajaran bahasa Inggris akibat metode pengajaran konvensional seperti pengajaran yang berpusat pada guru dan ceramah, yang membuat siswa menjadi pembelajar pasif. Masalah ini membutuhkan model pembelajaran yang inovatif dan menarik yang dapat meningkatkan partisipasi, motivasi, serta hasil belajar siswa. Penelitian kuantitatif ini mengkaji efektivitas bimbingan sebaya berbasis TGT dalam meningkatkan kemampuan pemecahan masalah siswa kelas V dalam mata pelajaran Bahasa Inggris. Penelitian ini melibatkan 50 siswa Sekolah Dasar Muhammadiyah Karangploso, yang dibagi secara merata menjadi kelas eksperimen (25 siswa) dan kelas kontrol (25 siswa). Data dikumpulkan menggunakan tes deskriptif yang dirancang berdasarkan indikator pemecahan masalah Polya dan dianalisis melalui uji normalitas, homogenitas, serta uji-t sampel independen menggunakan SPSS 30. Hasil menunjukkan adanya perbedaan yang signifikan antara kedua kelompok, dengan kelas eksperimen mencapai skor rata-rata pasca-tes sebesar 83,40, dibandingkan dengan 61,00 pada kelas kontrol. Temuan ini menunjukkan bahwa bimbingan teman sebaya berdasarkan TGT lebih efektif daripada metode pengajaran konvensional dalam meningkatkan kemampuan pemecahan masalah siswa. Kesimpulannya, model Bimbingan Sebaya berbasis TGT menawarkan metode strategis untuk meningkatkan kualitas pengajaran bahasa Inggris dan memperkuat kompetensi pemecahan masalah dalam konteks sekolah dasar.